Enzyme Kinetics Modeling as a Tool to Optimize Food Industry: A Pragmatic Approach Based on Amylolytic Enzymes - Galanakis, Charis M.; Patsioura, Anna; Gekas, Vassilis (My University, 2015)
Modeling is an important tool in the food industry since it is able to simplify explanation of phenomena and optimize processes that cover a broad field from manufacture to byproducts treatment. The goal of the current article is to explore the development of enzyme kinetic models and their evolution over the last decades. For this reason, corresponding simulations were classified in deterministic, empirical, and stochastic models, prior investigating limitations, corrections, and industrial applications in each case. The ultimate goal is to provide an answer to a major problem: how can we develop an intermediate complexity model that achieves satisfactorily representation of the main phenomena with a limited number of parameters?
Keywords: Michaelis–Menten; Monte Carlo; Multienzyme kinetics; Αmylases; Εmpirical models; Νeural networks